Odor-induced modification of oscillations and related theta-higher gamma coupling in olfactory bulb neurons of awake and anesthetized rats - Zhu, Ping; Liu, Shuge; Tian, Yulan; Chen, Yating; Chen, Wei; Wang, Ping; Du, Liping; Wu, Chunsheng (Frontiers in Chemistry, 2022)
Olfactory gamma oscillations (40-100 Hz) are generated spontaneously in animals and represent the activity of local olfactory bulb (OB) networks, which play important roles in cognitive mechanisms. In addition, high-frequency oscillations (HFO, 130‒180 Hz) have attracted widespread attention and are novel neuronal oscillations with a frequency range close to high gamma oscillations (60‒100 Hz, HGOs). Both HGOs and HFOs are distinctly regulated by θ rhythm in the hippocampus. To understand their mediation mechanisms in the OB, we investigated whether local field potential (LFP) oscillations including HGOs and HFOs and even their coupling with theta rhythm is modified by odor stimulation in both freely moving and anesthetized rats. Therefore, we combined electrophysiological technology and cross-frequency coupling analysis approaches to determine the difference in the odor-modulated LFP oscillations between awake and anesthetized rats. The obtained results indicate that LFP oscillations including HGOs and HFOs were differently modified by odor stimulation in both animals of two states. However, θ-HGOs and θ-HFOs coupling were modified in only awake animals. It is suggested that these oscillations and their interactions with theta oscillations may play crucial roles in olfactory network activity. This could pave the way to further understand the underlying mechanisms of oscillations in OB neurons towards odor sensation.